PERAN LITERASI MEDIA DALAM MEMAKNAI PESAN PEMASARAN POLITIK - Riefky Krisnayana (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
The phenomenon of the impact of internet technology on the political attitude of the public affects politicians in Indonesia. Politics is now a product that needs to be marketed as well as in commercial marketing. Through the imagery is expected to move the opinion to a better direction. With positive public opinion, the decision to vote becomes a necessity for politicians who are fighting in the political arena. Public opinion itself is a method of persuasion with a communication system through digital media that is direct and massive and can provide viral effects. Imagery becomes a very important part of the political marketing system. Political marketing itself is a practical method in the context of political communication, so it needs a media literacy movement designed to increase individual control over the media they use in interpreting the message.